Antibody Detection, Isolation, Genotyping, and Virulence of Toxoplasma gondii in Captive Felids from China - Yang, Yu-Rong; Feng, Yong-Jie; Lu, Yao-Yao; Dong, Hui; Li, Tong-Yi; Jiang, Yi-Bao; Zhu, Xing-Quan; Zhang, Long-Xian (Frontiers in Microbiology, 2017)
The felids are the only definitive hosts of Toxoplasma gondii, which could excrete oocysts into the environment and provide an infection source for toxoplasmosis in various warm-blooded animal species, particularly the captive felids that live close to human communities. The infection rate of the captive felids is a perfect standard in detecting the presence of T. gondii oocysts in the environment. In this study, sera or tissue samples from zoo (1 young tiger, 2 adult tigers, 6 young lions), farm (10 masked palm civets), and pet hospital (28 cats) from Henan Province (China) were collected. The sera (n=47) were tested for immunoglobulin G (IgG) antibodies against T. gondii by using modified agglutination test, whereas the hearts tissue (n=40) were bioassayed in mice to isolate T. gondii strains. The genotype was distinguished by using PCR-RFLP of 10 loci (SAG1, SAG2, SAG3, GRA6, BTUB, L358, c22-8, PK1, c29-2 and Apico). The detection rate for the T. gondii antibody in captive felids was 21.3% (10/47). One viable T. gondii strain (TgCatCHn4) was obtained from a cat heart tissue, and its genotype was ToxoDB#9. The oocysts of ToxoDB#9 were collected from a T. gondii-free cat. The virulence of TgCatCHn4 was low and no cysts were detected in the brain of mice at 60 days post inoculation. The finding of the present study suggested a widespread exposure of T. gondii for felids in Henan Province of central China, particularly those from the zoological gardens and homes. ToxoDB#9 was the predominant strain in China. Preventive measures against T. gondii oocyst contamination of various components of the environment should thus be implemented, including providing pre-frozen meat, well-cooked cat food, cleaned fruits and vegetables, monitoring birds and rodents, inactive T. gondii oocysts in felids feces, and proper hygiene.